Analisa Proksimat Jenis Daun Benalu dan Kelayakan Produk Sebagai Minuman Kesehatan: Analisa Proksimat Jenis Daun Benalu dan Kelayakan Produk Sebagai Minuman Kesehatan - Puji Astoko, Endro; Helilusiatiningsih, Nunuk; Setyo Utomo, Pamuji (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2025)
Mistletoe leaves are plants that stick to other plants but have not received much attention in their handling. The urgency of this research is that chemical treatment is very expensive and the side effects of chemical drugs are great, so mistletoe as an alternative natural ingredient can be used as an anticancer, antibacterial and other disease agent. The purpose of the study was to study the proximate content of 3 types of mistletoe leaves and the feasibility of the product as a health drink. The research method is a quantitative proximate test and product feasibility using the SWOT method. The raw materials tested were guava mistletoe leaves, mango mistletoe leaves and longan. The study was conducted from March to May 2025. The results obtained are as follows: proximate content includes water, protein, fat, carbohydrate, fiber in% is mango mistletoe leaves: 11.13 ± 1.22 | 7.19 ± 0.84 | 8.58 ± 0.41 | 54.25 ± 2.14 | 17.59 ± 0.83 | ; longan mistletoe leaves: 11.15 ± 1.05 | 14.25 ± 0.95 | 13.13 ± 0.34 | 51.25 ± 1.92 | 12.10 ± 0.72 |; water apple mistletoe leaves: | 12.58 ± 1.34 | 8.26 ± 0.63 | 11.30 ± 0.24 | 60.20 ± 2.31 | 14.65 ± 0.62 |. The product feasibility of 3 types of mistletoe leaves according to the SWOT analysis has the potential for health drinks. Longan mistletoe leaves have the potential to have the highest protein, fat and lowest fiber content compared to other types.